Proverbs - Wolters, Albert M. (Brill, 2020)
In the Proverbs volume in the Septuagint Commentary Series Al Wolters gives a meticulous philological commentary on the text of Proverbs as found in the important fourth-century Codex Vaticanus, together with a careful transcription of the Vaticanus Greek text and a fresh English translation thereof. The focus of the commentary is on the semantic and grammatical aspects of the Greek, relying primarily on general Greek usage rather than on the underlying Hebrew, and drawing on a broad array of lexicographical and grammatical resources, as well as a detailed examination of twelve previous translations of LXX Proverbs. In the process, many new interpretations of the often difficult Greek are proposed
10.1163/9789004425590
Keywords: Proverbs